Bolivia Final Report on Operational Activities : Rural Energy and Energy Efficiency - World Bank (Washington, DC, 2014)
When energy sector reforms were essentially completed in Bolivia in 1966, technical assistance initiatives in rural energy and energy efficiency picked up steam. Assistance was provided to the government to develop a sustainable market for rural energy. This development was guided by the following principles: the government role was that of regulator and facilitator; priority demand should be met at a municipal level and consumers decide whether a given rural energy project should be implemented; and the private sector should be encouraged to diversify energy supply in rural areas and to adopt the most sustainable and least costly combination of technologies. Halfway into the implementation of the rural energy component, it was realized that the use of biomass in rural areas needed special attention. An action plan was devised to provide a guide for the sustainable use of biomass energy services in rural areas and mitigate the impact of supplying and consuming biomass as an energy source. The National Biomass Program sets out energy policy options for creating regulatory and incentive mechanisms to promote the sustainable management of biomass. This approach will allow the biomass energy market to be integrated into the national energy market, balancing supply and demand and establishing defined value/price standards.